Pengaruh Penerapan E-System Perpajakan danPengetahuan Perpajakan Wajib Pajak Pada Kepatuhan WPOP - Purnama Dewi, Ni Putu Wina; Supadmi, Ni Luh (E-Jurnal Akuntansi, 2019)
E-Registration, e-Billing, and e-Filling are part of the e-System issued by the Directorate  General of Taxation as a modernization step in fulfilling tax obligations by taxpayers.  Knowledge of taxation is a key for taxpayers to comply with their tax obligations because  taxpayers who have knowledge of taxation understand the rules so they can fulfill their tax  obligations. This study aims to determine the effect of tax e-System implementation and  taxpayer tax knowledge on the level of individual taxpayer compliance at the Tabanan  Primary Tax Office. The data analysis method used is quantitative data analysis with  multiple linear regression analysis techniques. This type of research is primary data  obtained from the answers of individual taxpayers registered at the Tabanan Primary Tax  Office, namely the answers to a series of questionnaire questions submitted by researchers.  The results of this study indicate that the application of e-Registration, e-Billing, e-Filling,  and knowledge of taxpayer taxation has a positive effect on individual taxpayer compliance  at Tabanan Primary Tax Office. Keywords : E-Registration, e-billing, e-filling, taxpayer tax knowledge, tax compliance.